Radiative lifetimes, branching fractions, and oscillator strengths for highly excited levels in singly ionized tantalum (Ta ii). Issue 4 (29th December 2021) - Zhang, Lijun; Wu, Yaxin; Liu, Meina; Ma, Huiting; Quinet, Pascal; Dai, Zhenwen
ABSTRACT: Radiative lifetimes of 28 levels of Ta ii in the energy range 29256.907–55128.389 cm −1 were measured by time-resolved laser-induced fluorescence (TR-LIF) spectroscopy in laser-ablation plasma. Among the results, to our knowledge, 24 lifetimes are reported for the first time. These lifetimes, ranging from 2.7 to 111 ns, were combined with theoretical branching fractions obtained from pseudo-relativistic Hartree–Fock calculations including core-polarization effects to deduce semi-empirical transition probabilities and oscillator strengths for 284 Ta ii spectral lines.